Evaluation of Linkage Between the Corporate Economic Value-Added Analysis and Information Technology Using Big Data - S., Esakkiammal; Kasturi, K. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Businesses depend on the information technology and big data analytics to provide high-quality information, which can assist them in making better decisions and, ultimately, increase their performance. As a result, in order for businesses to reap the benefits of intelligent data, they are dramatically increasing the amount of money they invest in a wide variety of technologies and integrating them into their operational procedures. A lot of attention has been paid to the concept of agility as a strategic capability in today hypercompetitive corporate contexts. This is because it is predicted that information that is enabled by information technology will play a big role in the development of organizational capacities. In this paper, we develop an evaluation of linkage between the corporate economic value-added analysis (CEVA) and information technology using big data. The study carries out an analysis on corporate risk management by studying the corporate economic value-added analysis using both information technology chosen as model 1 and big data analytics as model 2. Three different corporate firms are used in the study and its economic relative to the model 1 and model 2 are studied. The study also measures the influence of solvency, profitability and liquidity on the Economic Value and Market Value in relation with information technology in corporate industry.